Evaluating the potential of green roofs for greywater treatment - Noor Suraya, Romali; M. I., Jemail; N. A. A., Artino; I. A., Mohamed (IOP Publishing Ltd., 2025)
Greywater, comprising household wastewater excluding toilet waste, represents a significant portion of daily wastewater. Effective greywater treatment is crucial to mitigate environmental pollution, especially when greywater flows directly into water bodie s without clear controls, discharge limits, and treatment requirements. Nature-based solution (NBS) approaches, such as green roofs, are gaining popularity for their urban benefits and potential for greywater treatment. However, in Malaysia, the application and literature on green roofs are limited, primarily focusing on stormwater management. The potential for greywater treatment remains understudied, despite numerous successful implementations worldwide. Hence, this study aims to explore the effectiveness of green roofs in improving greywater quality. Two green roof models were constructed: one using commercial materials and the other using recycled coconut waste. Greywater samples from washing and kitchen activities were tested, with influent and effluent samples analyzed for key water quality parameters including pH, turbidity, BOD, COD, TSS, TN, and TP. Both green roof models demonstrated notable effectiveness in reducing BOD concentrations, achieving removal efficiencies between 12% to 33%. The resulting BOD levels ranged from 21 to 25 mg/L, which is slightly above the limit of Standard A but compliant with Standard B of the Environmental Quality Act (EQA) 1974. While green roofs show potential in reducing BOD from greywater, their effectiveness in treat ing other water quality parameters remains limited. Addressing these shortcomings through system enhancements and integrated treatment approaches can lead to more robust and reliable greywater treatment solutions.